Advances in Lipid Nanoparticles for mRNA-Based Cancer Immunotherapy - Guevara, Maria L.; Persano, Francesca; Persano, Stefano (Frontiers in Chemistry, 2020)
Over the past decade, messenger RNA (mRNA) has emerged as potent and flexible platform for the development of novel effective cancer immunotherapies. Advances in non-viral gene delivery technologies, especially the tremendous progress in lipid nanoparticles’ manufacturing, have made possible the implementation of mRNA-based antitumor treatments. Several mRNA-based immunotherapies have demonstrated antitumor effect in preclinical and clinical studies, and marked successes have been achieved most notably by its implementation in therapeutic vaccines, cytokines therapies, checkpoint blockade and chimeric antigen receptor (CAR) cell therapy. In this review, we summarize recent advances in the development of lipid nanoparticles for mRNA-based immunotherapies and their applications in cancer treatment. Finally, we also highlight the variety of immunotherapeutic approaches through mRNA delivery and discuss the main factors affecting transfection efficiency and tropism of mRNA-loaded lipid nanoparticles in vivo.